P5: EFFECT OF VITAMIN C AND COLD ON GROWTH FACTOR RELEASE FROM PLATELET-RICH PLASMA. (27th April 2021) - Tomouk, T; Talaat, S; Smith, O; Mosahebi, A
Abstract: Introduction: Platelet-rich plasma (PRP) has gathered great momentum in surgery. The main outcome of the study was to assess whether there was a difference in growth factor release from PRP with addition of vitamin C, cooling, or both vitamin C and cooling. Method: Blood samples from 10 volunteers were centrifuged to produce PRP. Activated autologous thrombin was produced from platelet-poor plasma (PPP), which was added to PRP to activate it. PRP from each participant was then divided by activation method into three groups: A) cold pack only; B) vitamin C only; C) cold pack/vitamin C. Growth factor quantification was performed for human VEGF, IGF-1 and PDGF-AB using enzyme-linked immunosorbent assays. Result: At 24 hours, VEGF concentration in the cold group was significantly higher cf. the vitamin C group (p=0.02) and the cold/vit C group (p<0.01), whereas IGF concentration in the cold group was significantly higher cf. the vitamin C group (p=0.02) but not the cold/vit C group. At 1 hour and 24 hours, PDGF concentration in the cold group was significantly higher cf. both the vitamin C group (p<0.01) and the cold/vit C group (p=0.02 and p<0.0001 respectively). Conclusion: Cooling lead to increased growth factor release at 24 hours, indicating that cooling may lead to sustained release of growth factors. There was a trend for PRP treated with vitamin C to remain in a gel-like consistency rather than clot. This may prove useful in clinical practice where currently activated PRP is constrained to topical application only due to its consistency. Take-home message: Cooling may lead to sustained release of growth factors from platelet-rich plasma, whereas the addition of vitamin C may provide opportunity for injectable activated PRP.